Welcome to Westonci.ca, your go-to destination for finding answers to all your questions. Join our expert community today! Explore a wealth of knowledge from professionals across different disciplines on our comprehensive platform. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields.
Sagot :
You just put the y=5x+23 in -2x-y=5
-2x-(5x+23)=5
-2x-5x-23=5
-7x=5+23
-7x=28
X=-4
-2x-(5x+23)=5
-2x-5x-23=5
-7x=5+23
-7x=28
X=-4
Answer: if this doesn't help u let me know and i can explain more have a good day <3
x=−4 and y=3
Step-by-step explanation:
Step: Solvey=5x+23for y:
y=5x+23
Step: Substitute5x+23foryin−2x−y=5:
−2x−y=5
−2x−(5x+23)=5
−7x−23=5(Simplify both sides of the equation)
−7x−23+23=5+23(Add 23 to both sides)
−7x=28
−7x/−7=28/−7
(Divide both sides by -7)
x=−4
Step: Substitute−4 for x in y=5x+23:
y=5x+23
y=(5)(−4)+23
y=3(Simplify both sides of the equation)
Answer:
x=−4 and y=3
Thanks for stopping by. We are committed to providing the best answers for all your questions. See you again soon. We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. Stay curious and keep coming back to Westonci.ca for answers to all your burning questions.